2017
DOI: 10.1007/s11661-017-4062-5
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Powder Metallurgy Connecting Rod Preform During Hot Forging Based on Hot Compression and Finite Element Method Simulation

Abstract: Powder-forged connecting rod with a complex geometry shape always has a problem with nonuniform density distribution. Moreover, the physical property of preform plays a critical role for optimizing the connecting rod quality. The flow behavior of a Fe-3Cu-0.5C (wt pct) alloy with a relative density of 0.8 manufactured by powder metallurgy (P/M, Fe-Cu-C) was studied using isothermal compression tests. The material constitutive equation, power dissipation (g) maps, and hot processing maps of the P/M Fe-Cu-C allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…where h con is the contact heat conductivity and T roll is the roller temperature (K). For semi-solid rolling of aluminum alloy, the range of h con is 1000 to 5000 W/m 2 •K [26].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…where h con is the contact heat conductivity and T roll is the roller temperature (K). For semi-solid rolling of aluminum alloy, the range of h con is 1000 to 5000 W/m 2 •K [26].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, when the preform of the PF product is designed, the hot-deformation behaviour of the alloy is investigated first. According to the literature, some researchers have investigated the hot deformation of sintered alloys [13][14][15][16][17] to design the preforms of PF products. However, when the details of PF products are formed by material flow, both fully dense and not fully dense regions might co-exist during the forging process.…”
Section: Introductionmentioning
confidence: 99%
“…Using SEM coupled EMPA, Sengupta et al showed a high resolution picture of the shapes of bubbles and inclusions near the hook. Li et al investigated the micro structures of Ti‐CNTs mixed powders after ball milling using TEM. More recently, the ASPEX, which has the advantage of fast‐scanning and automatic analysis for a large number of inclusions in several hours, is popularized with prospects .…”
Section: Introductionmentioning
confidence: 99%